Abundance of eggplant (Solanum melongena L.) flower visitors in Lalitpur, Nepal - Mainali, R. P.; Thapa, R. B.; Giri, Y. P. (Journal of the Institute of Agriculture and Animal Science, 2018)
In order to determine the abundance of insect flower visitors in growing crop of eggplant, Solanum melongena L., a field experiment was conducted in Khumaltar, Laliptur during summer-rainy season of 2012 to 2014. The insect flower visitors were monitored weekly by end-to-end walk method using sweep net at different time of the day, viz. 7-8 am, 12-1 pm and 4-5 pm. Then collected insects were identified using the reference insects/books available in Insect Museum of Entomology Division, NARC, Khumaltar. This study revealed that Hymenopteran were found to be the most dominant (90.75%) flower visitors; followed by Lepidopteran insects (9.25%). Among the identified insect species, Bombus sp. (60.22%) was the most frequently collected bees as flower visitor of eggplant followed by Apis mellifera L., A. cerana F., Syntomis sp. in all three years of field study. Other flower visitors, such as Anthophora sp., Andrena sp. and Halictus sp. were also found visiting the eggplant flower but their occurrence was minimal. Significantly (p<0.05) higher number of insects visited the eggplant flowers at 7-8 am (58.48%) followed by those visiting during 4-5 pm (28.97%) and 12-1 pm (12.54%), respectively. For adequate pollination and healthy production of eggplant, conservation and utilization of flower visitors and their role in pollination is imperative. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page: 101-104